Maternal Mortality Care / 3 Overdue 4 Overly - Quranayati Quranayati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2022)
Preeclampsia is a hypertensive condition that occurs in pregnant women whose gestational age has reached 20 weeks or after delivery who previously had normal blood pressure and increased to 140/90 mmHg or more. Preeclampsia condition  is a vasospastic disease that involves many systems and is characterized by hemoconcentration, hypertension, and proteinuria >300 mg/24 hours. These symptoms can be seen during pregnancy, childbirth and in the puerperium which can be accompanied by convulsions and coma. Preeclampsia is one of the causes of maternal and perinatal mortality, and can be detected at gestational age >34 weeks with blood pressure < 140 /110 mmHg, then the patient may have preeclampsia.